2015
DOI: 10.1039/c4mh00097h
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-compatible eumelanin biointerface fabricated by chemically controlled solid state polymerization

Abstract: A high quality eumelanin thin film featuring efficient reversibility of the water induced conductivity switch and high biocompatibility was obtained,viaammonia-induced solid state polymerization of a 5,6-dihydroxyindole thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 49 publications
6
108
0
1
Order By: Relevance
“…These results showed that melanin thin films have great potential in the reconstruction of tissues, being biodegradable, and possess inflammatory response comparable to silicone. Another study of the biocompatibility of melanin thin films demonstrated that the melanin film effectively supports the growth of undifferentiated stem cells and their differentiation into neuronal precursors and neurons [146]. They related that high-quality melanin thin films display appealing features, such as reversible conductivity by controlled hydration-dehydration steps-excellent biocompatibility with stem cells, and water-resistant adhesion, for bioelectronic applications, e.g., in organic electrochemical transistors (OECTs), which can translate cellular activity into electrical signals [125,147].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…These results showed that melanin thin films have great potential in the reconstruction of tissues, being biodegradable, and possess inflammatory response comparable to silicone. Another study of the biocompatibility of melanin thin films demonstrated that the melanin film effectively supports the growth of undifferentiated stem cells and their differentiation into neuronal precursors and neurons [146]. They related that high-quality melanin thin films display appealing features, such as reversible conductivity by controlled hydration-dehydration steps-excellent biocompatibility with stem cells, and water-resistant adhesion, for bioelectronic applications, e.g., in organic electrochemical transistors (OECTs), which can translate cellular activity into electrical signals [125,147].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…An alternative route for eumelanin coating has been proposed recently, 41 which allows to overcome the main issues associated with the limited processability of eumelanins due to insolubility in most solvents. Typically, eumelanin thin films are obtained by direct deposition of the pigment from aqueous alkali favoring partial solubilization due to oxidative backbone modification.…”
Section: −10mentioning
confidence: 99%
“…The subsequent freezedrying at −60°C for 2 days afforded white cylindrical TOCNFaerogels with a final volume of 7 cm 3 , a bulk density d b of about 40 mg cm −3 , and a resulting porosity of 97.5%. TOCNFaerogels thus prepared were coated with eumelanin using the recently developed AISSP 41 of DHI (Scheme 2) and DHICA. Figure 2 shows complete aerogel coating, as apparent from the dark colorations, black in the case of DHI, or dark brown in the case of DHICA.…”
mentioning
confidence: 99%
“…15 Since the seminal work of McGinness 16 on electrical transport in eumelanin in 1974, many have endeavored to exploit eumelanin as a natural active material for bioelectronics. 10,[17][18][19] Understanding the nature of eumelanin conductivity is complicated by its heterogeneous nature, and two models for its structure exist: the extended…”
Section: Introductionmentioning
confidence: 99%